Implementation of Lean Construction To Reduce Project Delays - Ihsabaihaki, Ainur; Patriadi, Andi; Sajiyo, Sajiyo (Green Publisher Indonesia, 2025)
Delays in construction projects often result in resource waste and conflicts among stakeholders. This study focuses on the application of Lean Construction within the